Artificial Intelligence in Education: Use Without Violating the Principles of Academic Integrity - Palamar, Svitlana; Naumenko, Maryna (Educological discourse, 2024)
The article substantiates the relevance of issues related to the development of artificial intelligence, which allowed to form a clear understanding of modern AI tools. The prerequisites for the emergence and features of artificial intelligence as an international product are summarized. The author analyzes current trends in the field of artificial intelligence technologies. A list of popular AI technologies is presented and the current state of application of AI technologies by higher education students is determined. The article presents the results of a survey of higher education students of the Faculty of Pedagogical Education of Borys Grinchenko Kyiv Metropolitan University. The peculiarities of the use of artificial intelligence technologies by higher education students are determined. The advantages and negative consequences of the use of artificial intelligence in the education system are considered. The key issues related to the ethics of using AI in accordance with the principles and norms of academic integrity are described